Determination of the Value of Banking Companies in Indonesia with Profitability as a Mediation Variable - Soeharjoto Soeharjoto; Debbie Aryani Tribudhi (International Journal of Social Sciences and Humanities, 2026)
Purpose of this research is to analyze the influence of banking competition, the implementation of sustainable financial policies, with Net Interest Margin, Capital Adequacy Ratio, Loan to Deposit Ratio, Non-Performing Loan as control variables on the value of banking companies in Indonesia with profitability as a mediating variable and COVID-19 as a moderating variable. The sample was taken using purposive sampling with the criteria of banking stocks listed on the Indonesian Stock Exchange from 2018-2022. The research uses panel data regression with the unbalanced method. Results shown, Market Share, Herfindahl-Hirschman Index, Corporate Governance Index, Loans to Deposit Ratio, Non-Performing Loans, Market Share moderated by COVID-19, and Social Index moderated by COVID-19 were proven to have a negative and significant impact on Return on Assets. Economic Index, Environmental Index, Capital Adequacy Ratio, and Environmental Index moderated by COVID-19 were not proven to have a significant effect on Return on Asset. Social Index, Net Interest Margin, Herfindahl-Hirschman Index moderated by COVID-19, Economic Index moderated by COVID-19, and Corporate Governance Index moderated by COVID-19 were proven to have a positive and significant effect on Return on Asset. Return on Asset has been proven to have a positive and significant effect on Tobin’s Q, whereas Return on Asset moderated by COVID-19 has not been proven to have a significant effect on Tobin’s Q.